(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Photovoltaic power systems face two main challenges: inefficient power extraction under variations in irradiance and temperature, and DC bus voltage instability due to power mismatches. This paper outlines the development, modeling, and simulation of a standalone PV system with battery storage and DC-DC converters, employing a hybrid control strategy that simultaneously addresses these critical challenges. Maximum power point tracking is applied to enhance energy extraction from the PV array under perturbation conditions. A backstepping controller ensures accurate PV voltage tracking and maintains system stability under varying operating conditions. Moreover, to sustain the required constant DC bus voltage, a proportional–integral controller regulates battery charging and discharging. The proposed system is evaluated in MATLAB/Simulink under standard conditions to assess static stability and under varying irradiation, temperature, and load conditions to test the dynamic stability. A simulation study was conducted, and the results confirm improved power extraction and enhanced voltage stability, demonstrating the effectiveness of the proposed approach for DC microgrid applications.